Financial incentives to promote social mobility. (25th August 2009) - Forde, Ian; Zeuner, Dagmar
Abstract : Conditional cash transfer schemes have been shown to improve health and health behaviours in poorer countries. Ian Forde and Dagmar Zeuner wonder whether a similar strategy can work in the UK